The Dark Side of AI in Indonesian Education: Understanding Its Impact on the Alpha Generation in the Era of Technological Development - Sugihyono Sugihyono (Badan Penerbit STIEPARI Press, 2025)
This research was conducted to examine AI technology in education and its impact on Generation Alpha in the era of technological development. Education is the fundamental basis for shaping the character of the nation's generation, and with quality education supported by adequate facilities, the learning process will become more innovative. The presence of AI technology facilitates educational activities, from administration, data collection, to the creation of supporting learning media. In addition, children can learn more easily through any site, thus increasing interest in learning at school. However, AI does not only provide positive aspects, it turns out that various problems have been found for Gen Alpha towards AI, even to the point of addiction to using AI. So the impact on Gen Alpha is the emergence of immoral behavior, cultural changes due to imitating western cultural styles, and impolite attitudes and behaviors due to the influence of content on Tik Tok, Youtube and others. The next effect is a decrease in critical thinking skills due to dependence on finding instant answers through ChatGPT or AI. This is a challenge from the dark side of AI and at the same time a positive side in the progress of technological developments in the field of education. This research method uses a qualitative research approach with a focus on analysis and descriptive data obtained from various relevant sources, through a survey to one of the schools, and information from one of the subject teachers. Other sources used as references in this study mainly focus on journals as the main reference source, supported by news and books. The conclusion obtained from this study is that technology is important to use in the world of education, but there needs to be limitations given by teachers or schools to prevent children from accessing things outside of learning. In addition, teachers must be able to adapt to existing developments to be able to guide and direct their students to utilize AI technology as part of learning equipped with religious values in order to filter various cultural influences that enter without limits